Republic of Belarus : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for the Republic of Belarus. The assessment reveals that compliance supervision in Belarus is detailed with a strong culture of onsite examination. Two agencies exercise financial intelligence responsibilities. Money laundering offenses are investigated and successfully prosecuted. Some capacity exists to cooperate internationally. However, the legal framework is incomplete and, in some places, misdirected. Legislation criminalizing terrorist financing as a separate offense has not been adopted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet